Active Carbons and Their Reactivation in Non-Ferrous and Noble Hydrometallurgy (2008) - Viktor Mukhin (The Minerals, Metals and Materials Society, 2008)
"Among the methods proposed for spent activated carbon regeneration, the most acceptable is, thermal reactivation, because in this case the existing equipment for manufacture of activated carbon can be adapted for this purpose.In order to conduct the process of thermal re-activation of spent activated carbon directly at gold mills, a fullscale drum-type furnace with external electric heating has been developed, i.e. EPV-300 model with a throughput rate of 50 to 120 kg/hour. Its use ensures restoration of the adsorption properties of carbon up to the level of fresh activated carbon with an insignificant (by 0.7%) decrease in strength and with a high (95% to 97%) yield of reactivated carbon.During the recent years, activated powder carbon has been extensively used in flotation processes for treating polymetallic ores at ore treating plants to improve recoveries of main metals (copper, lead, nickel, etc.).Especially large volumes of activated powder carbon are used at the Talnakh concentrator of the Norilsk Mining and Metallurgical Complex in Russia for absorption of residual flotation reagents from recycled water in order to ensure efficient selective separation of minerals with similar physical and chemical properties.IntroductionSorption technology based on active carbons use starts being applied in such an important in the widest sense of the word strategical branch of economics as non-ferrous metallurgy. Thus since the middle ninetieth Russian gold extraction industry began to apply widely the processes of sorption from pulps and solutions by means of high-resistant granulated active carbons. That provided the start of gold ore minefield exploration, increasing of gold extraction from the ore and reducing its loss with the ""tails"" of process. At present more than 40% of Russian gold is extracted with the help of sorption technologies [1].Another field of active carbons application in non-ferrous metallurgy is the processes of non-ferrous ores floatation at ore-mining and processing enterprise. For that purpose powdered (less than l00µm) active carbons are used for providing the effective selection of minerals with similar physicochemical properties. This method not only increases the metal extraction level but provides deeper division of them."